2008
DOI: 10.1103/physrevb.77.041304
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature optical orientation of the exciton spin in cubicGaNAlNquantum dots

Abstract: The optical orientation of the exciton spin in an ensemble of self-organized cubic GaN / AlN quantum dots is studied by time-resolved photoluminescence. Under a polarized quasiresonant excitation, the luminescence linear polarization exhibits no temporal decay, even at room temperature. This demonstrates the robustness of the exciton spin polarization in these cubic nitride nanostructures, with characteristic decay times longer than 10 ns.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 28 publications
(77 reference statements)
3
27
3
Order By: Relevance
“…This high spin purity is in contrast to the initial predictions based on the much heavier effective masses and the smaller bulk spin-orbit splitting of GaN. It is, however, consistent with the long spin relaxation times observed in reference [74]. This surprising behavior can be explained considering the coupling terms in Hamiltonian A.3.…”
Section: Effect Of the Aspect Ratiocontrasting
confidence: 55%
See 2 more Smart Citations
“…This high spin purity is in contrast to the initial predictions based on the much heavier effective masses and the smaller bulk spin-orbit splitting of GaN. It is, however, consistent with the long spin relaxation times observed in reference [74]. This surprising behavior can be explained considering the coupling terms in Hamiltonian A.3.…”
Section: Effect Of the Aspect Ratiocontrasting
confidence: 55%
“…However, these built-in fields are negligible in ZB systems and much longer relaxation times are expected. Indeed, Lagarde et al [74] studied the exciton spin dynamics of self-assembled GaN/AlN ZB QDs and showed that the linear polarization persists up to room temperature and the spin relaxation times (exceeding 10 ns) are two or three orders of magnitude longer than in WZ phase.…”
Section: Magnetic-field Modulation Of the Hole Ground State In Cubic mentioning
confidence: 99%
See 1 more Smart Citation
“…[3,9] The ground state has F z = 3/2 symmetry, with a largely dominant |hh + component. [31] Yet, the minor components are important in determining the optical polarization and the hole spin dynamics.…”
Section: Effect Of the Aspect Ratiomentioning
confidence: 99%
“…[6] Lagarde et al showed that, as a consequence, the optical orientation in cubic structures is robust even at room temperature, with exciton spin lifetimes exceeding 10 ns. [9] These results hold promise for both optoelectronic and spintronic applications of cubic GaN/AlN QDs, and have triggered an increasing number of works investigating their properties. [2,10,11,12,13] An important aspect to understand such properties is the valence band mixing, which is known to underlie the optical polarization [13,14] and the exciton spin dynamics.…”
Section: Introductionmentioning
confidence: 99%